Water resources sector strategy : strategic directions for World Bank engagement. - World Bank. (Washington, DC : World Bank, 2004)
The strategy in this book focuses on how to improve the development and management of water resources while providing the principles that link resource management to the specific water-using sectors.
Includes bibliographical references.
oif 16/09/15
Loan
Keywords: World Bank; Water-supply -- Economic aspects -- Developing countries; Industrial water supply -- Developing countries -- Management; Economic development projects -- Developing countries -- Planning; Water-supply, Agricultural -- Developing countries -- Management; Water-supply -- Developing countries -- Management; Water resources development -- Developing countries -- Planning